Financial Management Within Young Workers in East Medan: The Role of Lifestyle, Job Position, and Financial Literacy with Income as a Mediator - Lestari, Sri Puji; Sari, Maya; Astuty, Widia; Fitri Wahyuni, Sri (AIBPM Publisher, 2025)
This study aims to examine how individual and socioeconomic factors, namely Lifestyle, Position, and Financial Literacy influence a person’s ability to manage their finances, with a particular focus on the mediating role of Income. Employing a quantitative and explanatory research approach, the study gathered data from 100 respondents and utilized path analysis through the PLS (Partial Least Squares) software to evaluate the relationships among the variables. The analysis reveals that Lifestyle, Position, Financial Literacy, and Income all have a direct and statistically significant effect on Financial Management. Furthermore, Lifestyle, Position, and Financial Literacy each have a notable impact on Income, suggesting their importance in shaping one’s earning potential. Income, in turn, functions as an effective mediator, strengthening the indirect effects of the three independent variables on Financial Management. These findings underscore the importance of financial awareness and personal development, especially for young workers in East Medan City. By enhancing their financial literacy, recognizing the influence of their social and occupational status, and applying intentional strategies in planning, budgeting, monitoring, and securing their finances, they can achieve better financial outcomes and long-term stability.